Synthesis of niosomes of diclofenac sodium and their microscopic evaluation - Muhammad Zaid; Khalil Ahmed; Awais Rasool; Muhammad Adeel (AMMANIF, 2020)
Objective: Incorporation of drugs into non-ionic surfactant vesicles (niosomes) during their manufacture affords a possible method of achieving controlled release. The aim of this study was to formulate niosomes as carriers for delivery of diclofenac sodium (DCS) to achieve controlled release. Method: Niosomes were prepared by Ether injection method using non-ionic surfactant (Span 80) and cholesterol in ratio of 1:1, the organic solvent (dichloromethane) and phosphate buffer. Results: The prepared niosomes were then evaluated for physical appearance, light microscopy, optical microscopy, transmission electron microscopy and entrapment efficiency. Conclusion: Diclofenac sodium niosomes were prepared successfully without using charge inducing surfaces and were confirmed by microscopic evaluation.